Lehrplanorientierte Inklusion hämophiler Kinder und Jugendlicher im Sportunterricht - Joeres, J.; Seuser, A.; Kurme, A.; Trunz-Carlisi, E.; Ochs, S.; Böhm, P. (Hämostaseologie, 2012)
Inclusive paedagogic thinking and acting is a modern and increasingly important topic in school sports. It will affect teachers as well as parents and students. The new international guidelines and national curricula enable new ways of inclusion especially for students with chronic illnesses like haemophilia. Special help from the sport teachers is of vital importance.In our project “fit for life” where we advice children and young adults with haemophilia to find their appropriate sport, we developed a new approach for an optimised inclusion of children with haemophilia into sport lessons. The whole project is running in corporation with the German Sport Teachers Association/ Hessen. We analysed and rated the actual curricula of the different school years and looked at the specific needs, risks and necessary abilities for persons with haemophilia. By this means we gathered about 600 typical movements and/or exercises for school sports and developed individual advice and adapted exercise solutions for sport lessons.
Keywords: Haemophilia; school sports; inclusion; fit for life